Stereoselective bile pigment binding to polypeptides and albumins: a circular dichroism study - Goncharova, Iryna; Urbanová, Marie (Analytical and bioanalytical chemistry, 2008)
Stereoselective recognition of bilirubin and biliverdin by poly(L-lysine) (PLL), poly(D-lysine) (PDL), and poly(L-arginine) (PLA) and their micelles with dodecanoate ions (C(12)) at different pH has been studied using a combination of vibrational and electronic circular dichroism. Biliverdin has been found to be more sensitive to pH in its complexes with the polypeptides. In acidic media in the complexes with PLL-C(12) and PDL-C(12) the conformation becomes more closed than the characteristic one found at physiological pH. Partial flattening and chiral self-association of bilirubin molecules takes place at higher concentrations with PLL and PDL. For both pigments, inversions of the ECD signals are observed in the systems with PLA at pH > or = 8.5. This study was carried out in order to clarify the role of Lys and Arg residues in pigment binding to serum albumin. The circular dichroism spectra obtained for bilirubin bound to different mammalian serum albumins have been compared with the homology within the IIA principal ligand-binding structural domains. Analysis suggests that the chiroptical properties of the pigment in the complexes with serum albumins depend on the location of Lys and/or Arg at positions 222 and 199 in the binding site.
Keywords: Animals; Hydrogen-Ion Concentration; vazba proteinů; lidé; Biliverdine; Albumins; Protein Binding; polylysin; peptidy; Bile Pigments; albuminy; Circular Dichroism; biliverdin; Polylysine; zvířata; žlučové pigmenty; koncentrace vodíkových iontů; cirkulární dichroismus; Peptides; Humans